Agriculture in Africa--Telling Myths from Facts : A Synthesis - Christiaensen, Luc (World Bank, Washington, DC, 2017)
Stylized facts drive research agendas and policy debates. Yet robust stylized facts are hard to come by, and when available, often outdated. In a special issue of Food Policy, 12 papers revisit conventional wisdom on African agriculture and its farmers' livelihoods using nationally representative surveys from the Living Standards Measurement Study-Integrated Surveys on Agriculture Initiative in six African countries. At times, the findings simply confirm the common understanding of the topic. But the studies also throw up several surprises, redirecting some policy debates while fine-tuning others. Overall, the project calls for more attention to checking and updating the common wisdom. This requires nationally representative data, and sufficient incentives among researchers and policy makers alike. Without well-grounded stylized facts, they can easily be profoundly misguided.